Antimicrobial Peptide Reverses ABCB1-Mediated Chemotherapeutic Drug Resistance - Luo, Xiaofang; Teng, Qiu-Xu; Dong, Jin-Yun; Yang, Dong-Hua; Wang, Meifeng; Dessie, Wubliker; Qin, Jiang-Jiang; Lei, Zi-Ning; Wang, Jing-Quan; Qin, Zuodong; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2020)
Multidrug resistance (MDR) of tumor cells to chemotherapeutic agents is the main reason for the failure of cancer chemotherapy. Overexpression of ABCB1 transporter that actively pumps various drugs out of the cells has been considered a major contributing factor for MDR. Over the past decade, many antimicrobial peptides with antitumor activity have been identified or synthesized, and some antitumor peptides have entered the clinical practice. In this study, we report that peptide HX-12C has the effect of reversing ABCB1-mediated chemotherapy resistance. In ABCB1-overexpressing cells, nontoxic dose of peptide HX-12C inhibited drug resistance and increased the effective intracellular concentration of paclitaxel and other ABCB1 substrate drugs. The mechanism study showed that peptide HX-12C stimulated ABCB1 ATPase activity without changing the expression level and localization patterns of ABCB1. Molecular docking predicted the binding modes between peptide HX-12C and ABCB1. Overall, we found that peptide HX-12C reverses ABCB1-mediated MDR through interacting with ABCB1 and blocking its function without affecting the transporter’s expression and cellular localization. Our findings suggest that this antimicrobial peptide may be used as a novel prospective cancer therapeutic strategy in combination with conventional anticancer agents.